Heat Transfer Simulation and Analysis of Electron Collector Based on Real-time Uniformity Detection Device of Irradiation Accelerator. Issue 1 (1st February 2023) - Zhang, Gefei; Yuan, Jushigang; Pang, Shiqiang; Huang, Jiang
Abstract: Beam scanning uniformity is an important parameter of electron irradiation accelerators, which affects the quality of irradiated products. Accurate measurements of beam scanning uniformity are required to evaluate accelerator performance. Currently, a set of devices is being developed to measure beam scanning uniformity under full beam conditions. However, the measurement device faces serious heating problems when the beam power is large. In this paper, the cooling structure of the electron collector is designed for the developed measurement device. The temperature distribution of the electron collector is simulated by ANSYS. The appropriate cooling flow rates are selected to ensure the thermal stability of the device when the total beam powers are 30 kW and 50 kW, respectively. The electron collector with a cooling structure is fabricated according to design parameters, and the experiment is carried out under a 1.5 MeV accelerator. The temperature is monitored by an infrared thermometer. The results show that the measured temperature is below the limit. The designed cooling parameters effectively solve the heating problem.